2022
DOI: 10.5603/gp.a2022.0090
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound imaging of abdominal muscles activity among women with stress urinary incontinence: case-control study in Poland

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
1
1
Order By: Relevance
“…"Sapsford, Hodges [17], Thompson and Neumann [6,11] have shown there is a synergistic contraction of the abdominoperineal muscles under normal conditions". Other authors have observed a synergistic co-contraction of the abdominal muscles when the PFM are contracted in both continent and incontinent women [9,25], as in this study. However, this synergism may be lost in incontinent women [26].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…"Sapsford, Hodges [17], Thompson and Neumann [6,11] have shown there is a synergistic contraction of the abdominoperineal muscles under normal conditions". Other authors have observed a synergistic co-contraction of the abdominal muscles when the PFM are contracted in both continent and incontinent women [9,25], as in this study. However, this synergism may be lost in incontinent women [26].…”
Section: Discussionsupporting
confidence: 78%
“…The TTC also tends to be higher in continent versus incontinent women. Neither of these two results showed statistically significant differences, as they have done in other studies [7,25].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation